Flour power : the practice and pursuit of baking sourdough bread - Jensen, Tara (Clarkson Potter/Publishers, 2022)
"A fun and empowering bread master class with 80 recipes and insights from sourdough whisperer Tara Jensen. Teacher and baker Tara Jensen introduces new and experienced bakers to approachable techniques and recipes for making sourdough, rye, and desem (hearty wheat) breads. Flour Power is divided into two parts: the workshop and the recipes. In the workshop, bakers learn all about flour and how to build strength in dough by hand, read a bread formula, and troubleshoot sluggish starters and unruly doughs. The recipes section is divided into chapters by flour and bread type. There's a chapter on sourdough using white flour (Olive Loaf; Milk Bread), whole wheat desem (Cinnamon-Raisin Desem; Aloo Paratha), and rye (Honey and Aniseed Rye; Mountain Rye). And like any good professor, Tara offers a chapter on extra credit too, with recipes like Overnight Waffles, Sourdough Pie Crust, and Cheddar Crackers to make from "discard" (the starter you discard before "feeding" it). Recipes are categorized by difficulty level and there's also a helpful "snapshot" at the top of each recipe offering a start-to-finish quick takeaway of the loaf from how much time it actually takes to the pan size you need and type of loaf the bread makes. Alongside stunning photography by Johnny Autry and playful, but informative illustrations are all the tips and tricks you'll need to become a happy and proficient baker at home"--